Cameroon : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2003)
The Poverty Reduction Strategy Paper (PRSP) assesses the main exogenous and endogenous risks affecting the implementation of the strategy, including terms-of-trade shocks and absorptive capacity weaknesses. The medium-term expenditure framework identifies the priorities and needs of the country to meet the Millennium Development Goals. The PRSP provides extensive sensitivity analysis of the impact of the main exogenous risks. The effective channeling of the resources freed from debt relief in favor of growth-enhancing and social development programs constitute a critical challenge for the government.